2021
DOI: 10.1016/j.sjbs.2021.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and expression of cyclic nucleotide gated ion channels 19 and 20 in Arabidopsis thaliana for their potential role in salt stress

Abstract: Cyclic nucleotide gated ion channels (CNGCs) in plants have very important role in signaling and development. The study reports role of CNGC19 and CNGC20 in salt stress in A. thaliana. In-silico, genome wide analysis showed that CNGC19 and CNGC20 are related to salt stress with maximum expression after 6 h in A. thaliana . The position of inserted T-DNA was determined ( in-vivo) through TAIL-PCR f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Previous studies have reported that plant AtCNGCs engage in biotic and abiotic stresses and that AtCNGC19 expression is elevated at increased NaCl concentrations. AtCNGC19 is involved in the tolerance of A. thaliana to high salt concentrations [ 49 , 50 ]. Similarly, BraGLR1 may help respond to salt stress by interacting with CNGC family members.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that plant AtCNGCs engage in biotic and abiotic stresses and that AtCNGC19 expression is elevated at increased NaCl concentrations. AtCNGC19 is involved in the tolerance of A. thaliana to high salt concentrations [ 49 , 50 ]. Similarly, BraGLR1 may help respond to salt stress by interacting with CNGC family members.…”
Section: Discussionmentioning
confidence: 99%
“…Under hot/cold and drought stresses, atcngc16 resulted in a greater than 10-fold stress-dependent reduction in pollen fitness and seed set ( Tunc-Ozdemir et al, 2013 ). Arabidopsis transgenic overexpressing AtCNGC19 or AtCNGC20 displayed salt tolerance and their knockout plants become more sensitive to the salt stress ( Oranab et al, 2021 ). Some AtCNGCs involved in the uptake and transport of heavy metal ions such as Pb 2+ and Cd 2+ .…”
Section: Ca 2+ Influxmentioning
confidence: 99%
“…When two or more channels create a complex and function as one unit, they are marked together. become more sensitive to the salt stress (Oranab et al, 2021). Some AtCNGCs involved in the uptake and transport of heavy metal ions such as Pb 2+ and Cd 2+ .…”
Section: Ca 2+ Influx Cyclic Nucleotide-gated Channelsmentioning
confidence: 99%
“…For example, 15 AtCNGCs ( AtCNGC1-10 / 12 / 14 / 16 / 18 / 20 ) are encoded Ca 2+ -permeable channels [ 8 ], and numerous studies confirm their functions in plant development, such as AtCNGC2 in leaf senescence, AtCNGC3 in germination, AtCNGC5 / 6 / 9 in root hair development, AtCNGC7 / 8 in male fertility, AtCNGC14 in root gravitropism and AtCNGC16 / 18 in pollen development [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Several AtCNGCs are involved in stress response, including AtCNGC1 / 10 / 19 / 20 in salt stress, AtCNGC2 / 4 / 11 / 12 in abiotic stress, AtCNGC2 / 5 / 6 / 9 / 12 in stomatal defense and AtCNGC6 in heat stress [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Together, these findings provide valuable references for functional characterization and application of CNGC genes in non-model plant species.…”
Section: Introductionmentioning
confidence: 99%